King Oscar II of Sweden and his connections with the Romanian freemasonry - Attila Carol Varga (Swedish Journal of Romanian Studies, 2024)
The present analysis represents a novel approach to the issue of Romanian-Swedish bilateral relations in the second half of the 19th century. This time, the focus is on the dimension of contacts between Romanian and Swedish Freemasonry. This was conducted in the second half of the 19th century by King Oscar II himself. In 1885 he made an official visit to Bucharest with Queen Sofia. On this occasion, he was made an honorary member of the Grand National Lodge of Romania (M.L.N.R.). Far from being merely a protocol award, it held a special significance. This visit underlined the desire of Constantin Moroiu, Grand Master of the Grand National Lodge of Romania, to gain international recognition for this Romanian Masonic powerIt was a very turbulent period in the history of Romanian Freemasonry, marked by a series of interventions by the Grand Orient of Italy in its internal affairs. With the award of this distinction, Romanian Freemasons sought to strengthen their internal unity through external recognition from all Masonic powers. To this end, the help of the Grand Lodge of Sweden was essential. The desire to consolidate the unity of Romanian Freemasonry was a natural reality, given the fact that Romania was proclaimed a Kingdom in 1881 and became a base of stability in this part of the continent.